Using Lixto for automating portal-based B2B processes in the automotive industry. (5th January 2005) - Baumgartner, Robert; Herzog, Marcus
In this paper, we propose an alternative method for facilitation of B2B process integration: front-side integration, which allows us to exploit existing web-based application infrastructure for business process integration across company borders. In this approach, so-called wrapper programs perform intelligent HTML to XML conversion in order to utilise the HTML output of web-based applications. Moreover, interaction with web-based user interfaces is automated to perform the appropriate actions on remote applications. Lixto technology converts web applications of collaborative (and even non-collaborative) business partners into programmatically accessible information sources, similar to web services, however without requiring any changes on the partner's IT infrastructure. We will give a concrete example of how to set up such a business process integration application in the automotive industry domain.